Preparation and Application of Superhydrophobic Copper Mesh by Chemical Etching and In-situ Growth - Tong, Qilei; Fan, Zhenzhong; Wang, Biao; Liu, Qingwang; Bo, Yunhe; Qian, Liqing (Frontiers in Chemistry, 2021)
Oily sewage and floating oil in the ocean have a huge threat to the ecological environment, and the preparation of oil-water separation materials has been a significant issue. In this study, the super-hydrophobic oil-water separation copper mesh prepared by the chemical etching method and the in-situ growth method and the performance evaluation are introduced. The oxide layer on the surface of the copper mesh is first removed by pickling, and then immersed in a ferric chloride solution for chemical etching to make the surface rough, stearic acid is used for in-situ growth to reduce the surface energy, a super-hydrophobic oil-water separation copper mesh is obtained. The contact angle of the copper mesh can reach more than 160°. The copper mesh is chemically stable and can effectively adsorb floating oil and separate the oil-water mixture. After several oil-water separation experiments, the oil-water separation efficiency can still be above 97%. The study used a simple and environmentally friendly method to prepare the oil-water separation copper mesh, which has important application significance for water quality restoration.